2018
DOI: 10.1111/arcm.12414
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Destructive Survey of Early Roman Copper‐Alloy Brooches using Portable X‐ray Fluorescence Spectrometry

Abstract: This paper argues that portable X-ray fluorescence spectrometry (pXRF) is a suitable elemental measurement technique to study the production of copper-alloy artefacts. However, rather than try to imitate the accuracy and precision of laboratory techniques, it is more beneficial to deploy it in a survey role, one that attempts to model chronological and geographical changes within large quantities of artefacts. To achieve this, it was investigated to what extent corrosion and the issues surrounding surface meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…5.3.9-5.3.16). This approach is effective for the basic identification of alloy types (Tate 1986, 23), as once interesting alloy groups are identified, the data can be usefully interpreted in a qualitative manner, following the method proposed by Roxburgh et al (2018;also see Rehren 2002, 146). A more targeted analysis from a selected bracelet group is then applied, in order to gain a comparative measurement for an uncorroded surface.…”
mentioning
confidence: 99%
“…5.3.9-5.3.16). This approach is effective for the basic identification of alloy types (Tate 1986, 23), as once interesting alloy groups are identified, the data can be usefully interpreted in a qualitative manner, following the method proposed by Roxburgh et al (2018;also see Rehren 2002, 146). A more targeted analysis from a selected bracelet group is then applied, in order to gain a comparative measurement for an uncorroded surface.…”
mentioning
confidence: 99%
“…(Bruker's Yellow filter) provided a good count rate for the elements of interest. Assays of artefacts were taken for 60 s each, which was sufficient time to obtain stable results and was in line with other researchers using similar instruments [5,31,32]. Nine modern copperbased alloy reference standards were used for the calibration of these data (Table A1).…”
Section: Discussionmentioning
confidence: 69%
“…For analysis of copperbased alloys, we found that operating the x-ray tube with a setting of 40 keV at 5.0 µA in an air-path and through a window composed of 12 mil Al and 1 mil Ti filters (Bruker's Yellow filter) provided a good count rate for the elements of interest. Assays of artefacts were taken for 60 seconds each, which was sufficient time for the count rates to stabilise, and is in line with other researchers using similar instruments [25,72,73]. Each reference standard was analysed twice and the results averaged.…”
Section: Appendix a Portable X-ray Fluorescence Calibration Proceduresmentioning
confidence: 72%